Temporary Work: The Gendered Rise of a Precarious Employment Relationship - Vosko, Leah F. (University of Toronto Press, 2000)
The first in-depth analysis of temporary work in Canada, this book by Leah F. Vosko examines a number of trends, including the commodification of labour power; the decline of the full-time, full-year job as a norm; and the gendered character of prevailing employment relationships. Spanning the period from the late nineteenth to the late twentieth century, Temporary Work traces the evolution of the temporary employment relationship in Canada and places it in an international context. It explores how, and to what extent, temporary work is becoming the norm for a diverse group of workers in the labour market, taking gender as the central lens of analysis." "Recent scholarship emphasizes that the nature of work is changing, citing the spread of non-standard forms of employment and the rise in women's participation in the labour force. Vosko confirms that important changes are indeed taking place in the labour market, but argues that these changes are best understood in historical, economic, and political context. This book will be invaluable to academics in a variety of disciplines as well as to policy analysts and practitioners in government, industry, and organized labour. –Publisher's descsription
Book available at Internet Archive to readers with print disabilities: https://archive.org/details/temporaryworkgen0000vosk/mode/2up
Keywords: 1900-1999; Canada; Canadá; Convenio de la OIT; Division sexuelle du travail Canada Histoire 20e siècle; Estados Unidos; Etats-Unis; Femmes Travail Canada Histoire 20e siècle; History; ILO Convention; ILO Recommendation; Recomendación de la OIT; Sexual division of labor; Sexual division of labor Canada History 20th century; Temporary employment; Temporary employment Canada History 20th century; Travail temporaire Canada Histoire 20e siècle; USA; Women Employment; Women Employment Canada History 20th century; agence de travail temporaire; agence pour l'emploi privée; agencia de empleo privada; collective bargaining; comentario; comment; commentaire; condiciones de empleo; conditions d'emploi; conditions of employment; contrat de travail; contratación; contrato de trabajo; convention de l'OIT; cuadros estadísticos; developed countries; discriminación por razones de sexo; discrimination fondée sur le sexe; division du travail basée sur le sexe; división del trabajo por sexo; domestic worker; empleo temporal; emploi temporaire; employment security; employé de maison; empresa de trabajo temporal; femmes mariées; flexibilidad del trabajo; flexibilité du travail; formación; formation; histoire; historia; history; immigrant; inmigrante; labour contract; labour flexibility; labour force participation; labour legislation; legislación del trabajo; législation du travail; married women; migrant workers; mujeres casadas; negociación colectiva; négociation collective; papel de la OIT; pays développés; países desarrollados; private employment agency; protección social; protection sociale; recommandation de l'OIT; recruitment; recrutement; role of ILO; rôle de l'OIT; salaire; salario; seguridad en el empleo; sex discrimination; sexual division of labour; sindicalización; social protection; statistical table; syndicalisation; sécurité de l'emploi; tableau statistique; tasa de actividad de mano de obra; taux d'activité; temporary employment; temporary work agency; tendance; tendencia; trabajador doméstico; trabajador migrante; trabajadoras; trade unionization; training